Bioquality and the flora of Japan: an investigation into the factors that influence the distribution of rare endemic plant species of the Japanese flora - Jones, B (2021)
With two in five plant species threatened with extinction, the identification, evaluation, and prioritisation of plant communities requiring intervention is of critical importance. Whilst Japan is one of 36 global biodiversity hotspots, this is a broad scale assessment, limiting its value and application at finer scales or management levels. Bioquality is a term that applies to a (plant) community and emphasises the concentration of high conservation value elements of biodiversity within it, global rarity, and taxonomic distinctiveness, and does not encompass the separate issue of predicted threats to be treated in a separate analysis. Bioquality assessments can be applied meaningfully at various spatial resolutions.